Yasmine Gooneratne: Jane Austen, Australia and Sri Lanka - Gillian Dooley (Literature)
In 1967, when she was a lecturer in English at the University of Ceylon, Yasmine Gooneratne (1935–2024) wrote an article on English literature in Ceylon for an English journal. Three years later, Gooneratne’s study of Jane Austen was published in Cambridge University Press’s ‘British Authors: Introductory Critical Studies’ series. In 1972, she moved to Australia with her husband, Brendon. Although by this time she had published two volumes of poetry, her first novel, A Change of Skies, was not published until 1991. It concerns a Sri Lankan linguistics academic who moves to Australia with his wife, and the adjustments they have to make to Australian ways. Since then, she published two more novels, The Pleasures of Conquest (1996) and The Sweet and Simple Kind (2009). In this paper I will attempt to draw together these three coordinates in Gooneratne’s career: English literature, especially Jane Austen; Australia; and Sri Lanka. What did Gooneratne learn, as a novelist, from her study of Austen? How did her time in Australia influence her as a novelist? And how did she negotiate the difficulties she identified in her fellow Sri Lankan writers?